Kendali Optimal Model Pertumbuhan Mikroalga dalam Chemostat - Wahyuni Ningsih; Henny Purwaningsih; Rofilah El Maghfiro (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2022)
Microalgae is one of Indonesia's natural potentials that can be utilized in various needs such as producing energy products (bioethanol, biodiesel), biopolymer producing plastic and as a soil mixture for construction engineering, even as waste treatment by absorbing the remaining organic compounds and nutrients or absorb some of the hazardous compounds contained in the waste. One of the microalgae culture media is chemostat. Chemostat is a type of continuous bioreactor that functions for the cultivation of microalgae and other microorganisms that are usually used in laboratory and industrial scales. In this study, control efforts on the microalgae growth model in the chemostat were carried out. This is so that the growth of microalgae reaches the equilibrium value in the minimum possible time. By applying Pontryagin's Minimum Principle and dilution parameters as control variables, it is obtained that the type of control carried out is bang-bang control. Then the control problem is solved numerically using the ICLOCS2 toolbox. The simulation results showed that microalgae were able to reach equilibrium conditions faster by 40.9% under the control. So, it can be said that the system can be controlled optimally.